THE EFFECT OF BIOLOGICAL MEMBRANES TO FIBROBLAST PROLIFERATION: PLATELET-RICH FIBRIN RELEASATE VS AMNIOTIC (Research report) - Rezmelia Sari; Sri Pramestri Lastianny; Alya Nur Fadhilah (Dentino : Jurnal Kedokteran Gigi, 2019)
Background: Both amniotic and platelet-rich fibrin membranes are used to enhance open wound healing process clinically. The growth factors of these membranes are almost similar but the certain mechanism is still unclear especially in inducing fibroblast proliferation. Objective: to compare the effect of both membranes to fibroblast proliferation. Methods: This in vitro study was using fibroblast from periodontal ligament. The fibroblasts were cultured and then divided into 3 groups: fibroblasts with PRF releasate membrane (group I), fibroblasts only (group II), and fibroblasts with amniotic membranes (group III). The cells were observed in 24, 48 and 72 hours. Proliferation was tested by MTT assay and data was analyzed by two-way ANOVA followed by post-hoc test. Results: It showed that PRF releasate membrane induced fibroblast proliferation higher than amniotic in the first 24 hours meanwhile amniotic induced it two-fold in the next 24 hours. However, in the following time there were no significant differences between groups. Conclusion: It can be concluded that PRF membranes and amniotic membranes have the ability to accelerate proliferation of fibroblasts but have different effects at the time of induction.